ESG controversies and bank risk-taking and value: does ESG governance matter? - Mahyoub, Mugahed; Ja’afar, Roslan; Ab Ghani, Nur Laili (2023)
Environmental, social, and governance (ESG) plays a crucial role in the literature and attracts increasing interest among practitioners, financial scholars, and policymakers. Nonetheless, little is known about how ESG controversies impact bank risk-taking and the value and role of ESG governance dynamics in this relation. As a consequence, this study intends to investigate the effect of ESG controversies on bank risk-taking and value and proposes the interaction role of ESG governance dynamics over the aforesaid relationship. The study sample comprised of banks in emerging markets and the data cover the period from 2015 to 2021. The data pertinent to this study will be gathered from the Refinitiv Eikon database using a panel data analysis technique. This study is unique since it sheds new insight into how ESG governance dynamics may impact the ESG controversies and bank risk-taking and value association. Study findings will provide bank management, practitioners, and policymakers with a new insight into how ESG governance dynamics influence ESG controversies and risk-taking and the value of banks. Most importantly, how ESG governance serves as a means to alleviate management disputes.